Determinants of Poverty in Indonesia: An Islamic Perspective - Amir Machmud, Yusuf Murtadlo Hidayat; Eeng Ahman (International Journal of Advanced Science and Technology, 2020)
This study aims to analyse the factors that affect poverty in Indonesia in the Islam perspective. The variables identified refers to the Qur’an (QS 30:41, QS 3: 180, QS 70:18 and QS 2: 275) that are human-nature crimes, the concern of the rich to the poor, and the practice of usury in economic life. The data used is panel data of 12 provinces in Indonesia sourced from the Central Bureau of Statistics, Bank Indonesia, and Baznas during the period 2012-2017. The data that has been collected is then analysed by using random effect regression analysis. The results show that poverty in Indonesia in the Islamic perspective affected by the practice of usury and the ignorance of the rich to the poor. This finding implies that to alleviate poverty in an Islamic perspective it is necessary to abolish the practice of usury, maisyir and ghoror and the need for the concern of the rich towards the poor through optimizing zakat, infaq, and endowments.